2014
DOI: 10.1159/000360734
|View full text |Cite
|
Sign up to set email alerts
|

A Nasally Applied Cellulose Powder in Seasonal Allergic Rhinitis in Adults with Grass Pollen Allergy: A Double-Blind, Randomized, Placebo-Controlled, Parallel-Group Study

Abstract: Background: A nasally applied cellulose powder is increasingly used in many countries as a remedy for allergic rhinitis. In 2009, a 4-week study in birch pollen-allergic children showed a reduction in nasal symptoms. The best effect occurred on days with lower pollen counts. The present study in grass pollen-allergic adults used the same basic design. Methods: In May 2013, a double-blind, placebo-controlled study was conducted in 108 patients with allergic rhinitis due to grass pollen (18-40 years of age). SMS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 40 publications
2
31
1
Order By: Relevance
“…Our randomized, double-blind, placebo-controlled study has shown a similar efficacy of NCP and the placebo in clinical symptom scores, nasal eosinophil counts, and objective measurements of nasal airflow limitation. These results are in contrast to those of previous double-blind placebo-controlled studies, which have demonstrated the efficacy of NCP over the placebo treatment in patients with birch pollen AR, in terms of reductions in symptom scores811 and rescue medication use 9. These differences may be explained from the amount and presence of allergen exposure to AR patients.…”
Section: Discussioncontrasting
confidence: 94%
See 2 more Smart Citations
“…Our randomized, double-blind, placebo-controlled study has shown a similar efficacy of NCP and the placebo in clinical symptom scores, nasal eosinophil counts, and objective measurements of nasal airflow limitation. These results are in contrast to those of previous double-blind placebo-controlled studies, which have demonstrated the efficacy of NCP over the placebo treatment in patients with birch pollen AR, in terms of reductions in symptom scores811 and rescue medication use 9. These differences may be explained from the amount and presence of allergen exposure to AR patients.…”
Section: Discussioncontrasting
confidence: 94%
“…However, several previous studies have evaluated the efficacy of NCP in patients who have stopped the use of intranasal steroids or have never used them before and during the enrollment,8911 which is similar to our study. A recent study has demonstrated the efficacy of NCP in enhancing oxymetazoline-increased PNIF in adults with moderate to severe persistent perineal AR 24.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The formation of a gel layer lining the nasal epithelia means that CP has the capacity of CP to protect the nasal mucosa from direct contact with aeroallergens that would readily trigger allergic inflammatory responses [9]. Administration of CP via Nasaleze TM (Kisska International Ltd., Keighley, UK), the most extensively applied device for intranasal dosing, is effective in restoring nasal epithelial mucus thickness and reducing sensitization to aeroallergens in patients with seasonal AR [10].…”
Section: Introductionmentioning
confidence: 99%
“…Recent clinical trials confirmed the effectiveness and safety of CP for the management of AR [9, 11, 12]. In contrast, another study demonstrated that CP conferred no significant effect on ameliorating dust mite-sensitized AR children [13].…”
Section: Introductionmentioning
confidence: 99%